2019
DOI: 10.3748/wjg.v25.i20.2463
|View full text |Cite
|
Sign up to set email alerts
|

Brucea javanica oil emulsion improves the effect of radiotherapy on esophageal cancer cells by inhibiting cyclin D1-CDK4/6 axis

Abstract: BACKGROUND Esophageal cancer is one of the most common cancers around the world, and it has high incidence and mortality rates. The conventional therapy for esophageal cancer is radiotherapy, although its effect is highly limited by the resistance of esophageal cancer cells. Thus, strong radiosensitizers can be very crucial during radiotherapy against esophageal cancer. Brucea javanica oil emulsion (BJOE) is a widely used drug against various cancers, such as liver, colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…As uncovered in the previous study, BJOE could regulate the relative tumor genes to kill cancer cells directly [ 22 – 25 ]. Besides, it had also been verified to repress the resistance reaction of tumor cells to chemotherapy and significantly improve body immunity [ 26 ]. To further understand the function of BJOE on endometrial cancer cells, the cellular activity of RL95-2 was observed for 48 h after the single BJOE (50 μ g/mL), the single H-MnO 2 -PEG, or the combination of H-MnO 2 -PEG/BJOE by CCK-8 assay and DAPI assay.…”
Section: Resultsmentioning
confidence: 99%
“…As uncovered in the previous study, BJOE could regulate the relative tumor genes to kill cancer cells directly [ 22 – 25 ]. Besides, it had also been verified to repress the resistance reaction of tumor cells to chemotherapy and significantly improve body immunity [ 26 ]. To further understand the function of BJOE on endometrial cancer cells, the cellular activity of RL95-2 was observed for 48 h after the single BJOE (50 μ g/mL), the single H-MnO 2 -PEG, or the combination of H-MnO 2 -PEG/BJOE by CCK-8 assay and DAPI assay.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclin D1 regulates the activity of Cyclin-dependent kinase (CDKs) [20,21]. Cyclin D1 is the functional subunit of CDK4 and regulates the G1/S transition of cells [22]. CDK4 belongs to the Ser/Thr protein kinase family.…”
Section: Mir-29a Targetes Vegf To Module the Expression Of Apoptosis mentioning
confidence: 99%
“…Brucea javanica (L.) Merr. (Ya-dan-zi in Chinese, Simaroubaceae) is a crucial Chinese folk medicine widely used for the treatment of dysentery, which was also known as inflammatory bowel disease (IBD) [ 8 , 9 ]. Brucea javanica oil (BJO), an extract of the desiccative ripe fruit of the Brucea javanica (L.) Merr., exhibits various bioactivities, including anti-inflammatory, antimalarial, and antitumor activities [ 10 ].…”
Section: Introductionmentioning
confidence: 99%